MANAJEMEN PERAN SERTA MASYARAKAT DALAM PENGEMBANGAN SEKOLAH - Nugraha Suharto; Edy Sofyan (STKIP Subang, 2022)
Kepmendiknas No. 044/U/2002, the government provides a forum for the community to participate and channel their aspirations in supporting education through the Board of Education at the district level and the School Committee in each education unit or group of education units (schools). With the existence of the Education Council and school committee, the level of concern and participation of the community in helping the government realize quality education is expected to be better and increase to realize community-based education. Implementation of Kepmendiknas No. 044 / U / 2002 there are several problems that need to be resolved immediately, including: (1) Not all communities and education stakeholders in the regions understand Kepmendiknas No. 044 / U / 2002 concerning Education Councils and School Committees; (2) Not all districts and schools have implemented Kepmendiknas No. 044/U/2002 as appropriate; (3) There are still many people who do not understand the School Committee, and consider the School Committee to be the same as the Education Organizing Auxiliary Board (BP3); and (4) The impact of the Board of Education and the School Committee has not had much effect on improving the quality of educational services and learning outcomes. With the decentralization model of education, schools as educational units that have been a very passively empowered need to be encouraged to become strong, independent, professional institutions in providing optimal services to students and the community. This is the core of school-based management (SBM) which is applied especially in primary and secondary education in the country. One of the most important elements in this management is the role of society represented through boards of education and school committees.